Midlife crisis the feminist origins of a chauvinist cliché - Schmidt, Susanne 1988- (The University of Chicago Press, 2020)
"This book recounts the surprising origin story of the "midlife crisis." Before becoming a gendered cliché, the midlife crisis gained traction as a feminist concept with the publication of journalist Gail Sheehy's best-selling Passages: Predictable Crises of Adult Life. Coined by psychoanalyst Elliott Jaques in the 1950s, the term was largely neglected until Sheehy re-invented it as a feminist idea that challenged the double standard of middle age. Widely popular, 'midlife crisis' was subsequently appropriated and redefined as a masculinist concept by psychological and psychiatric experts. Susanne Schmidt's telling reveals the midlife crisis' remarkable role in modern American life: first to valorize the emergence of female breadwinners and dual-income families, then to reassert gender order in times of social change. A must-read"--
Keywords: Geschichte; Psychologie; Feminismus; Midlife-Crisis; Sheehy, Gail / Passages; Midlife crisis; Midlife crisis / History; Feminist psychology / United States / History; Psychology / United States / History / 20th century; Feminist psychology; Psychology; United States; 1900-1999; History